Enhanced melt crystallization of biobased Poly(ethylene 2, 5-furandicarboxylate) by low loading of octavinyl-polyhedral oligomeric silsesquioxanes. (June 2020) - Liu, Yang; Qiu, Zhaobin
Abstract: Through a common solution and casting process, a biobased poly(ethylene 2, 5-furandicarboxylate) (PEF)/octavinyl-polyhedral oligomeric silsesquioxanes (ovi-POSS) composite was successfully prepared at low loading of ovi-POSS in this research. The melt crystallization of PEF was apparently enhanced by low loading of ovi-POSS as a nucleation agent in the composite, displaying a higher melt crystallization peak temperature at a constant cooling rate and a shorter crystallization half-time at the same crystallization temperature. Ovi-POSS did not modify the crystallization mechanism and crystal structure of PEF in the composite. Highlights: A biobased PEF/ovi-POSS composite was prepared at low loading of ovi-POSS. Ovi-POSS obviously enhanced the melt crystallization of PEF. The enhanced crystallization of PEF arose from the nucleation effect of ovi-POSS. Both PEF and its composite displayed the α form crystal structures.